What You Know, What You Do, and How You Feel: Cultural Competence, Cultural Consonance, and Psychological Distress - Dressler, William W.; Balieiro, Mauro C.; dos Santos, José E. (Frontiers in Psychology, 2018)
Describing the link between culture (as a phenomenon pertaining to social aggregates) and the beliefs and behaviors of individuals, has eluded satisfactory resolution; however, contemporary cognitive culture theory offers hope. In this theory, culture is conceptualized as cognitive models describing specific domains of life that are shared by members of a social group. It is sharing that gives culture its aggregate properties. There are two aspects to these cultural models at the level of the individual. Persons have their own representations of the world that correspond incompletely to the shared model—this is their ‘cultural competence.’ Persons are also variable in the degree to which they can put cultural models into practice in their own lives—this is their ‘cultural consonance.’ Low cultural consonance is a stressful experience and has been linked to higher psychological distress. The relationship of cultural competence per se and psychological distress is less clear. In the research reported here, cultural competence and cultural consonance are measured on the same sample and their associations with psychological distress are examined using multiple regression analysis. Results indicate that, with respect to psychological distress, while it is good to know the cultural model, it is better to put it into practice.